Relationship of King Taksin and Chophaya Nakon (Noi) - พัฒนถาบุตร กนกชน; วงศ์สุรวัฒน์ โกวิท (Thai Interdisciplinary and Sustainability Review, 2019)
The purpose of this research was to study the relation between King Taksin and Chophaya Nakon (Noi). Did such relation affect the local politics of Nakhon Sri Thammarat and the regional politics after the era of King Taksin in 1782 ? The research finding shows that the significance of the relation between the 2 personages could be mediated through the characters as follows: Chophaya Nakon Noo who is the grandfather of Chophaya Nakon (Noi), Chophaya Nakon Pat who is the legitimate father of Chophaya Nakon (Noi), and the Concubine Prang, known later on as “Lady Prang”, was the mother of Chophaya Nakhon (Noi). In other words, King Taksin was thought to be the first to establish a policy assigning a royal son to rule the strategic southern city of Nakhon Sri Thammarat through presenting the Concubine Prang during her second month of pregnancy to the Viceroy to the City of Nakhon Sri Thammarat who was then appointed Chophaya Nakhon Sri Thammarat. King Taksin foresaw the importance of Nakhon Sri Thammarat to be second most strategic to Thonburi, for this reason, appointed Chonakon, the father of the Concubine Prang, to rule Nakhon Sri Thammarat’s colonies as well as to serve as the power base for his unborn son. Although the kingdom was then ruled by the Chakri Dynasty and had considerable impacts on Nakhon Sri Thammarat in every aspect, such policy established at the end of King Taksin’s era continued to last relying on close friendship and network relation which favored Chophaya Nakhon Noi’s remarkable rise to power in Nakhon Sri Thammarat and to rule more southern territories than any Chophaya could.